Operando methods: A new era of electrochemistry - Yang, Yao; Feijóo, Julian; Briega-Martos, Valentín; Li, Qihao; Krumov, Mihail; Merkens, Stefan; De Salvo, Giuseppe; Chuvilin, Andrey; Jin, Jianbo; Huang, Haowei; Pollock, Christopher J.; Salmeron, Miquel B.; et al. (Current Opinion in Electrochemistry, 2023)
One of the grand challenges facing electrochemistry is to directly resolve the complex nature of (electro)catalyst active sites and capture real-time “movies” of reaction dynamics, i.e. “watching chemistry in action”. The need for such fundamental understanding has stimulated the development of operando/in situ methods, which have greatly enhanced our ability to identify activity descriptors of electrocatalysts and establish structure–property relationships of energy materials. This review summarizes the frontiers of operando electrochemical liquid-cell scanning transmission electron microscopy and correlative synchrotron X-ray methods, which are complementary tools to comprehensively investigate reaction dynamics across multiple spatiotemporal scales. In an effort to encourage greater adoption of advanced operando methods by the general electrochemistry community, this review points out the need to benchmark electrochemistry in confined and heterogenous liquid environment with minimal beam-induced damage. We anticipate that multimodal operando methods will become indispensable for understanding interfacial reaction mechanisms for the broad chemistry and energy materials communities.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Electrocatalysis; Electrochemical interfaces; Energy materials; Operando methods; Scanning transmission electron microscopy; Synchrotron X-rays